Analysis of Interpersonal Communication, Motivation and Attitudes towards the Implementation of Patient Safety in Hospital Inpatients - Nabilatul Fanny; Liss Dyah Dewi Arini (International Journal of Health and Medicine, 2024)
The background to this research is that effective integration of interpersonal communication, motivation and attitudes can strengthen the implementation of patient safety in the health service environment, especially in inpatient settings. The aim of this research is to analyze whether there is an influence of Interpersonal Communication, Motivation and Attitude on the implementation of Patient Safety. The stages of achievement in this research include several stages of observation, sample determination, using a cross sectional approach using a questionnaire and data processing using a data analysis method using multiple linear regression tests. This research method is collecting primary data by giving questionnaires to all nurses who are directly involved in efforts to provide services to all patients at Jati Husada Karanganyar General Hospital with a cross sectional design, the sample size is 69 nurses. The research data was then tested for linear regression at a significance level of 0.005. The results of this research are that the level of understanding and implementation of patient safety in the Jati Husada Karanganyar Hospital inpatient is good, which is 89.7% for the level of understanding (interpersonal communication, motivation and attitude), on the variables of Interpersonal Communication, Motivation and Attitude simultaneously. has a significant effect on the implementation of patient safety in the Jati Husada Karanganyar Hospital, which means that the higher the value of interpersonal communication, motivation and attitude, the more disciplined the nurses are in carrying out patient safety procedures, the variables Interpersonal Communication, motivation and attitude have a significant effect on the implementation of patient safety in Inpatient care at Jati Husada Karanganyar Hospital, where the influence is positive, which means that the better the nurse's attitude in implementing patient safety procedures, the higher the level of patient safety implementation.